1997
DOI: 10.1152/physrev.1997.77.3.627
|View full text |Cite
|
Sign up to set email alerts
|

Properties and regulation of the minK potassium channel protein

Abstract: The minK gene encodes a protein of 130 amino acids that has a single transmembrane segment and is expressed in many tissues including heart, uterus, and kidney. When Xenopus oocytes are injected with minK mRNA, a very slowly activating voltage-dependent potassium current is induced in these cells. The induced channels appear to result from the interaction of the minK protein with other channel-forming subunits such as the KvLQT1 channel. The minK protein is intimately associated with the structure of the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…However, little is known about whether delayed rectifier K + currents, which are sensitive to volatile anesthetics, is present in the central nervous system. It has been reported that KVLQT1 is strongly expressed in human heart and pancreas (32), and KCNE1 mRNA is abundant in the kidney, submandibular gland, and the uterus (33,34). However, both are hardly expressed in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about whether delayed rectifier K + currents, which are sensitive to volatile anesthetics, is present in the central nervous system. It has been reported that KVLQT1 is strongly expressed in human heart and pancreas (32), and KCNE1 mRNA is abundant in the kidney, submandibular gland, and the uterus (33,34). However, both are hardly expressed in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, other small molecules produced in eukaryotic cells can form pores. For example, a 27-amino-acid fragment of the so-called minK potassium channel forms a cation pore by forming a homotetramer (1,18). Nonetheless, it seemed unlikely to us that one cryptdin 3 peptide could form a channel, because the size of the molecule (ϳ4 kDa) would appear to preclude a single peptide from having the multiple membrane spanning domains usually required for channel formation.…”
Section: A Potential Mechanism For Cryptdin 3 Channel Formationmentioning
confidence: 99%
“…I sK , or MinK, a potassium channel protein sharing little similarity with other cloned potassium channels, induces very slow voltage-dependent K ϩ channel activity in Xenopus oocytes expression system (5). It has only 130 amino acids and a single putative transmembrane domain.…”
mentioning
confidence: 99%
“…Expression of MinK in Xenopus oocytes or in HEK293 cells can induce a unique slowly activating voltage-dependent K ϩ -selective current that closely resembles native I sK , the slowly activating and non-inactivating K ϩ channel current well characterized in heart (5,10). Key experiments in Xenopus oocytes suggested that the MinK protein was a regulator of expressed channel activity and not sufficient by itself to form functional I sK channels (11,12).…”
mentioning
confidence: 99%